Effect of Prolonged Starvation of Nacella concinna, Odontaster validus, and Sterechinus neumayeri on Their Body Composition and the Enrichment of the Aquatic Environment with Nitrogen and Phosphorus - Arkadiusz Nędzarek; Katarzyna Stepanowska (Water, 2024)
The seasonal availability of food for Antarctic zoobenthic consumers affects, among other factors, the levels of excreted metabolites that can serve as a source of nitrogen (N) and phosphorus (P) for autotrophs. This study tested the effects of prolonged starvation on N and P excretion by Nacella concinna, Odontaster validus, and Sterechinus neumayeri, as well as changes in their body chemistry. In all animals starved for 65 days, a significant decrease in body protein content was observed (33% for S. neumayeri and approximately 23% for N. concinna and O. validus). Nitrogen excretion rates were higher than phosphorus, with mean values (in µmol N or P h−1 100 g−1) of 1.351 and 0.094 for N. concinna, 0.779 and 0.037 for O. validus, and 0.538 and 0.075 for S. neumayeri, respectively. Ammonium nitrogen accounted for 50% to 69% of total nitrogen, while total reactive phosphorus represented 35% to 42% of total phosphorus. The study confirmed the natural adaptation of zoobenthos to prolonged food scarcity and demonstrated that (i) protein was the primary energy source during starvation, (ii) excretion rates were negatively correlated with invertebrate body size and were higher for N than P, and (iii) the excreted N and P loads may serve as a source of nutrients for autotrophs and act as chemical signals in trophic chemoreception.